2021
DOI: 10.1111/head.14103
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to care in episodic and chronic migraine: Results from the Chronic Migraine Epidemiology and Outcomes Study

Abstract: Objective: To assess rates of and factors associated with traversing fundamental barriers to good medical outcomes and pharmacologic care in individuals with episodic migraine (EM) and chronic migraine (CM), including socioeconomic status and race.Background: Barriers to good outcomes in migraine include the lack of appropriate medical consultation, failure to receive an accurate diagnosis, not being offered a regimen with acute and preventive pharmacologic treatments (if indicated), and not avoiding medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 52 publications
0
62
0
1
Order By: Relevance
“…The mTOQ-4 was derived from the mTOQ-6 by selecting the items that best assessed efficacy: "2-h pain free, " "24-h relief, " "able to plan, " and "in control. " Each item is rated never (1), rarely (2), less than half the time (3), or half the time or more (4). Patients were grouped by baseline mTOQ-4 total scores into the following optimization categories: very poor (0), poor (1-5), moderate (6-7), and maximal (8) than 14% having maximal optimization (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mTOQ-4 was derived from the mTOQ-6 by selecting the items that best assessed efficacy: "2-h pain free, " "24-h relief, " "able to plan, " and "in control. " Each item is rated never (1), rarely (2), less than half the time (3), or half the time or more (4). Patients were grouped by baseline mTOQ-4 total scores into the following optimization categories: very poor (0), poor (1-5), moderate (6-7), and maximal (8) than 14% having maximal optimization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high burden of migraine, highlighting the need for effective therapy, migraine remains underdiagnosed and undertreated [3]. Less than half of those with migraine seek medical care and receive a migraine diagnosis [4]. Ideally, preventive treatment should reduce the frequency, severity, and duration of migraine episodes, while slowing disease progression [5].…”
Section: Introductionmentioning
confidence: 99%
“…Migraine diagnostic delay is due to the time-consuming traditional headache care delivery approach involving a clinic visit, shortage of headache-trained providers, and the growing burden of primary headache disorders worldwide. 2 , 12 , 89 , 90 Given the increase in the global burden of migraine estimated to affect a billion people, 9 it would not be possible to capture every patient with migraine seeking the traditional in-person clinical visits. Hence, the SSI phone interview of patient history is the closest approach analogous to the traditional method of migraine diagnosis—making it our preferred “gold standard” for remote diagnosis in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Diagnostic delay increases the risk of chronic migraine, treatment refractoriness, comorbidities, and medication overuse. 2 Of nine headache-related variables in a 7-year follow-up study, a 6-month delay in migraine diagnosis was the only factor differentiating headache freedom from persistent headache. 10 Another 10-year longitudinal study showed a 2-fold increased risk of persistent migraine in children diagnosed after age 12.…”
Section: Introductionmentioning
confidence: 93%
“…Episodic migraine (EM) with or without aura is a diagnosis that can reflect occasional or frequent (<8) migraine days per month and likely makes up the bulk of headache sufferers that regularly present to their doctor with a complaint of head discomfort that disrupts activity. 9,10 Most of the time all that is required for the patient to see this as a manageable problem is a diagnosis and effective acute therapy. 11 When occasional headaches are very severe, leading to frequent hospital presentations, time off work or difficulty in caring for family members, a preventive should be considered.…”
Section: Acute Therapies Diagnosis and Management Principlesmentioning
confidence: 99%